2021
DOI: 10.1021/jacs.0c11006
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatics and Electrochemistry: Mechanism and Scope of Charge-Transfer Reactions on the Surface of Tribocharged Insulators

Abstract: The phenomenon of surface electrification upon contact is a long-standing scientific puzzle, with for instance written accounts of charged samples of amber attracting feathers dating back to the 600 B.C. Electrostatic hazards associated with electrical insulators subject to mechanical friction are well documented, and the design of commercial products, such as copiers and laser printers, is based on the static charging of electrical insulators. Nonetheless, the physical-chemical origin of this phenomenon remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 70 publications
0
22
0
Order By: Relevance
“…The FEP film shows best output performance ( Q tr = 30.7 nC, I sc = 52.0 nA, and V oc = 77.0 V), and the surface charge density (based on the area of tater droplet) is calculated to be 153.5 μC m –2 (Note S3), but the Kapton film presents the worst one ( Q tr = 1.0 nC, I sc = 2.4 nA, and V oc = 2.1 V), and the charge density is only 5.1 μC m –2 . Figure S9 in the Supporting Information presents a comparison of the surface charge densities reported in recent years, it can be seen that the charge density of this work has the highest result. ,,, The results are mainly related to electron affinity, ionization energy, and surface hydrophobicity of different triboelectric materials (see Note S4 in the Supporting Information). ,,, The wetting property of different triboelectric films is investigated by water contact angle measurement, as shown in Figure S10 in the Supporting Information. The FEP film has the highest output performance, because of its greater ability to acquire electrons and better surface hydrophobicity.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…The FEP film shows best output performance ( Q tr = 30.7 nC, I sc = 52.0 nA, and V oc = 77.0 V), and the surface charge density (based on the area of tater droplet) is calculated to be 153.5 μC m –2 (Note S3), but the Kapton film presents the worst one ( Q tr = 1.0 nC, I sc = 2.4 nA, and V oc = 2.1 V), and the charge density is only 5.1 μC m –2 . Figure S9 in the Supporting Information presents a comparison of the surface charge densities reported in recent years, it can be seen that the charge density of this work has the highest result. ,,, The results are mainly related to electron affinity, ionization energy, and surface hydrophobicity of different triboelectric materials (see Note S4 in the Supporting Information). ,,, The wetting property of different triboelectric films is investigated by water contact angle measurement, as shown in Figure S10 in the Supporting Information. The FEP film has the highest output performance, because of its greater ability to acquire electrons and better surface hydrophobicity.…”
Section: Resultsmentioning
confidence: 70%
“…38,43,49,50 The results are mainly related to electron affinity, ionization energy, and surface hydrophobicity of different triboelectric materials (see Note S4 in the Supporting Information). 37,46,51,52 The wetting property of different triboelectric films is investigated by water contact angle measurement, as shown in Figure S10 in the Supporting Information. The FEP film has the highest output performance, because of its greater ability to acquire electrons and better surface hydrophobicity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, studies have shown that solids, liquids and even gases will be charged due to contact separation 48,49 . This is because gas is also composed of molecules and atoms.…”
Section: Lightning Formation Mechanism and Near Surface Atmospheric Electric Field During Geological Methane Emission In Permafrost Regiomentioning
confidence: 99%
“…Fortunately, over the last 5–10 years, a growing number of research groups have noticed one type of electrostatic field, which can be simply generated by contact electrification without any applied voltage or additives. Static charges develop on the surface of electrically insulating materials that are first brought in contact with and then macroscopically separated from another solid. , Recent studies show that this phenomenon is not limited to the solid/solid interface but also occurred at the liquid/solid or liquid/liquid interface. Based on the contact charging at the liquid/solid interface, our group developed a self-powered droplet triboelectric nanogenerator with spatially arranged electrodes as a probe for measuring the charge transfer (CT) between liquid and solid interfaces and showed that the electron transfer is the dominant CT species in the case of liquid/solid contact . This inevitably raises a challenge about the reproducibility of the chemical reaction in the liquid solution as chemical reactivity is governed by the movement and transfer of electrons, and electron transfer is most likely to occur at the interface between the reaction solution and the surrounding environment or the container, , such as air, beaker and pipette, when preparing the reaction solution.…”
Section: Introductionmentioning
confidence: 99%